Development of Interactive Learning Media Using the Lectora Application to Enhance Student’s Critical and Creative Thinking Skills - Marlina, Deby; Sari, Silvi Yulia; Rahim, Fanny Rahmatina (Journal of Innovative Physics Teaching, 2024)
The Development of Interactive Learning Media in the 2013 Curriculum is a government effort to ensure that students have 21st-century skills. The goal of the conducted research is to develop valid interactive learning media on the topic of Newton's Law of Gravity. A field study revealed that students' critical and creative thinking skills in Newton's Law of Gravity were still low. Therefore, the existing problem was addressed by producing a product in the form of integrated learning media that fostered critical and creative thinking skills for high school students. The research conducted followed the Research and Development (R&D) approach using the ADDIE model, which was reduced to the Implementation stage. Three Physics lecturers from the Faculty of Mathematics and Natural Sciences Education at State University of Padang (UNP) were involved in this research as validators, along with six Physics teachers from Padang City as practitioners. Validity test sheets were used as the data collection instrument in this research. During the data analysis phase, instrument validation and product validation were performed using the V Aiken Model Technique. The research results showed that the validated development instrument for the product category was valid. The average validity test score for the product was 0.79, which falls into the valid category. Therefore, it can be concluded that the interactive learning media developed in this study is considered valid.